Will Individual Actions Do the Trick? Comparing Climate Change Mitigation Through Geoengineering Versus Reduced Vehicle Emissions. Issue 3 (11th March 2021) - Murray, Emily G.; DiGiorgio, Andrea L.
Abstract: Geoengineering is the focus of a large debate over potential solutions to climate change. However, in the midst of geoengineering and other large‐scale proposals, such as reducing emissions at an industrial level, the role of individual actions to reduce emissions is often overlooked. Given the current and fast‐paced changes we have seen as emissions are reduced by COVID‐19 social distancing strategies, it is time to re‐examine the impact that individual actions can have. This paper considers how one individual action (reducing carbon dioxide emissions from gasoline‐fueled private vehicles), when adopted at a global scale, may have an effect that is comparable to the effects of geoengineering. This paper also argues that the role of geoengineering as a safeguard against climate change may be encouraging complacency and reducing motivation for individual action. Plain Language Summary: As global temperatures continue to rise, several types of solutions are being considered to mitigate climate change. One of these is geoengineering—the large‐scale use of technology coupled with and enhancing Earth's natural processes. Geoengineering is the focus of a large debate over potential solutions to climate change since, while different geoengineering solutions may help curb CO2 concentrations, they remain largely untested and may pose greater risks. Further, it has been argued that, as we consider geoengineering and other large‐scale proposals, we risk the public losing sight of the potential for their individual actions to reduce emissions, and instead putting more faith in science to save us from climate change. Given the current and fast‐paced changes we have seen as emissions are reduced by COVID‐19 social distancing strategies, it is time to re‐examine and reinforce the impact that individual actions can have. This paper considers how one individual action (reducing CO2 emissions from private vehicles), when adopted at a global scale, may have an effect that is comparable to that of geoengineering. This paper also argues that the role of geoengineering as a safeguard against climate change may be encouraging complacency and reducing motivation for individual action. Key Points: Replacing private vehicles with electric or hybrid vehicles could significantly mitigate climate change compared to geoengineering It is important that the portrayal of geoengineering as a safeguard does not reduce motivation for emission cuts